A review of the main tectonic settings of Palaeo-and-Mesoarchean ore deposits in the northern São Francisco Craton, NE Brazil. Issue 21 (30th November 2022) - Barbosa, Johildo Salomão Figueirêdo; Gordilho Barbosa, Rafael; Leitzke, Felipe Padilha; de Menezes Leal, Angela Beatriz; Luciano, Rejane Lima; da Cruz Filho, Basílio Elesbão; Santana, Jocilene; de Moraes, Antônio Marcos Vitória
ABSTRACT: This work is based on the unprecedented Tectonic-Geochronological Map of Bahia (TGMBA): metallogenic implications. In the TGMBA, sixteen tectonic domains were identified, and the main mineral occurrences and deposits in each were recorded. Of the Palaeo-Mesoarchean blocks, the Gavião (GB), Serrinha (SB) and Uauá (UB) blocks were highlighted. The southern GB was formed by plate tectonics, in two stages, at ca. 3403–3378 and 3259–3240 Ma. These rocks served as basement for the Umburanas Greenstone Belt, which comprises felsic metavolcanic rocks (3147 Ma) interspersed with ocean floor mafic metavolcanics and could have been the source of the recently found orogenic gold. This crust could also have formed the basal section of the Brumado metavolcanic-sedimentary sequence, which hosts one of the most important magnesite mines in the world. The northern part of the GB hosts TTGs with ages of ca. 3642–3520 Ma, the oldest known rocks in the whole São Francisco Craton. This region served as a passive margin for the Jacobina-Umburanas Sea, where quartzites and conglomerates (3305 Ma) with detrital gold were deposited and, in the deeper portions of this sea, Mesoarchean ocean floor or Island-arc basalts (3200 Ma) with pillow-lava structures were formed. On the platform of this basin, Mn deposits were formed in association with pelites and sandstones